The impact of macroeconomic measures on the valuation of listed equity in the US. Insights from high inflation periods - Dominik Novak (Managerial Economics, 2025)
While the relationship between stock prices and macroeconomic indicators in the US has been widely examined, conflicting findings in the empirical literature suggest the presence of nonlinear dynamics that remain insufficiently explored. Following the work of A. López-Villavicencio and V. Mignon (2011), and A. Brick and D. Nautz (2008), inflation rates above a threshold level of 3% to 5% are associated with significant adverse effects on economic stability and stock market volatility. Therefore, there is a notable gap in the literature regarding the interactions between macroeconomic measures and stock prices during periods of elevated inflation, focusing on potential threshold effects. This study examines these relationships using monthly data from August 1973 to August 1982, representing High-Inflation Period 1, and from January 2021 to June 2024, representing High-Inflation Period 2. The analysis compares the direction and magnitude of the relationships across both periods. The results confirm that hedging against price level increases is a stronger determinant than withdrawal from capital markets due to heightened uncertainty caused by rising inflation rates, which would otherwise lead to declining stock prices. Additionally, the results highlight a strategic shift in US monetary policy, leading to better-anchored inflation expectations. The analysis also indicates that industrial production has become a less reliable proxy for economic activity in recent years, reflecting the US economy’s transition towards a service-oriented structure. Overall, the observed cointegration between stock prices and macroeconomic variables challenges the assumptions of the Efficient Market Hypothesis.